Models of medical center business processes to improve decision-making efficiency - Grinchenko, Marina; Kutsenko, Dmytro (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2025)
The subject of the article is the process of digitizing laboratory test results and formalizing the business processes of a medical center in order to develop an information system focused on intelligent data analysis. The goal of this work is to design models that formalize the business processes of a medical center in interaction with patients, enabling the identification of areas that require automation to improve the efficiency of medical services. The following tasks were solved: analyzing the current state of medical data digitalization and the issues related to the unification of laboratory test results; examining the organization of business processes in a medical center and the interaction of its key participants; developing a conceptual and functional model of service delivery; and constructing a business process model that reflects the structured organization of the institution’s activities in interaction with patients. The following methods include SWOT and PEST analyses of the medical center, examination of internal and external documentation, analysis of the existing database and algorithms for providing medical services, the IDEF0 functional modeling methodology, and the BPMN business process modeling approach. The obtained results: an analysis of existing solutions and studies was conducted; the results of SWOT and PEST analyses of the medical center were presented; a conceptual model of medical service organization was created; a functional model was built considering regulatory, organizational, and clinical aspects; and a BPMN-based model of key business processes was developed. Business processes requiring automation using intelligent data analysis methods were identified, forming the framework of the future information system. Conclusions: the proposed models provide a scientific and methodological foundation for automating the collection and processing of laboratory test results, their standardization, and integration into a unified information framework of the medical center. This will enhance the efficiency of the medical center’s business processes in interaction with patients, reduce the time required for processing diagnostic results, minimize the risk of errors, and ensure high-quality support for the provision of medical services.